2018
DOI: 10.1107/s2053230x18009834
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Fc fragment of the NIST reference antibody RM8671

Abstract: The structure of the Fc fragment of the NIST reference antibody RM8671 is described in an orthorhombic crystal form. The molecular conformation is compared with those of precedents using a CH3-based reference frame and the pronounced asymmetry is linked to packing interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…Potential Iron-Binding Site of NISTmAb. The crystal structure of the fragment crystallizable (Fc) region of the NISTmAb (PDB 5VGP) 47 was visualized with PyMOL as shown in Figure 11A. Interestingly, negatively charged oxygen atoms of the side chain carboxylate groups of Asp 252 and Glu 261 are located rather close to the side chain hydroxyl oxygen atom of Thr 259 , with distances of 7.4 and 5.8 Å, respectively.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Potential Iron-Binding Site of NISTmAb. The crystal structure of the fragment crystallizable (Fc) region of the NISTmAb (PDB 5VGP) 47 was visualized with PyMOL as shown in Figure 11A. Interestingly, negatively charged oxygen atoms of the side chain carboxylate groups of Asp 252 and Glu 261 are located rather close to the side chain hydroxyl oxygen atom of Thr 259 , with distances of 7.4 and 5.8 Å, respectively.…”
Section: ■ Discussionmentioning
confidence: 99%
“…However, CPA samples for M255 and M431 trend more closely to the 0.3 % Nox regression line ( Figures 7B,D ), indicating decreased protein A binding is more closely associated with oxidation at these sites. Previous reports have indeed demonstrated that oxidation in the Fc region disrupts protein A binding as it binds to a region where M255 and M431 are located and where the C H 2 and C H 3 domains interact ( Deis et al, 2015 ; Gallagher et al, 2018 ). In the above example, it is our position that if a specific residue is a causal factor in reducing binding, then alteration of the kinetics of that oxidation (e.g., slowed via ligand-bound protection) will not alter the trend of relative binding vs. site-specific %Met oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…g Representative 2D class averages of Tie2 dimeric mutant/hTAAB IgG1 complex (Top). Cyclical higher-order structure of the Tie2 dimer/hTAAB IgG1 complex in 4-to-4, 5-to-5, and 6-to-6 assemblies were modeled based on the 2D class averages of tetragonal, pentagonal, and hexagonal closed-ring structures, respectively, using crystal structures of the Tie2 Fn2–3/chimeric hTAAB Fab complex, Tie2 Ig1–Fn1 (PDB: 4K0V 11 ) and Fc fragment of human IgG1 (PDB: 5VGP 57 ) (bottom). Scale bars, 20 nm.…”
Section: Resultsmentioning
confidence: 99%